The Role of Religiosity and Financial Literacy in the Adoption of Islamic Digital Services in Indonesia - Muttaqien, Muhammad Khaerul; Kartika, Rini Fatma; Sopa, Sopa; Idrus, Ali (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2025)
This study investigates the key determinants of consumer preference for digital services provided by Islamic financial institutions in Indonesia. It examines the influence of relative advantage, Sharia financial literacy, Islamic religiosity, and initial trust on consumer preference. A sample of 524 respondents was analyzed using structural equation modeling (SmartPLS 4.0.9.9). The results show that relative advantage and Sharia financial literacy significantly influence initial trust, which in turn positively impacts consumer preference. Islamic religiosity was found to significantly influence Sharia financial literacy but not consumer preference directly. However, it plays a moderating role in strengthening the relationship between relative advantage and consumer preference. These findings offer both theoretical and practical implications by enhancing our understanding of digital service adoption in a religious financial context and providing strategic insights for Islamic financial institutions aiming to improve digital service engagement.======================================================================================================== ABSTRAK - Peran Religiositas dan Literasi Keuangan dalam Adopsi Layanan Digital Islam di Indonesia. Penelitian ini menyelidiki faktor-faktor utama yang memengaruhi preferensi konsumen terhadap layanan digital yang disediakan oleh lembaga keuangan syariah di Indonesia. Penelitian ini menelaah pengaruh keunggulan relatif, literasi keuangan syariah, religiositas Islam, dan kepercayaan awal terhadap preferensi konsumen. Sebanyak 524 responden dianalisis menggunakan pemodelan persamaan struktural (SmartPLS 4.0.9.9). Hasil penelitian menunjukkan bahwa keunggulan relatif dan literasi keuangan syariah berpengaruh signifikan terhadap kepercayaan awal, yang pada gilirannya berdampak positif terhadap preferensi konsumen. Religiositas Islam terbukti berpengaruh signifikan terhadap literasi keuangan syariah, namun tidak secara langsung terhadap preferensi konsumen. Namun demikian, religiositas Islam berperan sebagai variabel moderasi yang memperkuat hubungan antara keunggulan relatif dan preferensi konsumen. Temuan ini memberikan implikasi teoritis dan praktis, baik dalam memahami adopsi layanan digital dalam konteks keuangan berbasis agama maupun dalam menyediakan wawasan strategis bagi lembaga keuangan syariah untuk meningkatkan keterlibatan layanan digital.